Structural basis for selectivity in a highly reducing type II polyketide synthase - Du, Danyao; Katsuyama, Yohei; Horiuchi, Masanobu; Fushinobu, Shinya; Chen, Aochiu; Davis, Tony D.; Burkart, Michael D.; Ohnishi, Yasuo (Nature chemical biology, 2020)
In type II polyketide synthases (PKSs), the ketosynthase–chain length factor (KS–CLF) complex catalyzes polyketide chain elongation with the acyl carrier protein (ACP). Highly reducing type II PKSs, represented by IgaPKS, produce polyene structures instead of the well-known aromatic skeletons. Here, we report the crystal structures of the Iga11–Iga12 (KS–CLF) heterodimer and the covalently cross-linked Iga10=Iga11–Iga12 (ACP=KS–CLF) tripartite complex. The latter structure revealed the molecular basis of the interaction between Iga10 and Iga11–Iga12, which differs from that between the ACP and KS of Escherichia coli fatty acid synthase. Furthermore, the reaction pocket structure and site-directed mutagenesis revealed that the negative charge of Asp 113 of Iga11 prevents further condensation using a β-ketoacyl product as a substrate, which distinguishes IgaPKS from typical type II PKSs. This work will facilitate the future rational design of PKSs. Structures of the ketosynthase–chain length factor complex from ishigamide biosynthesis, cross-linked to the acyl carrier protein, reveal the molecular interactions between these domains and how the reaction pocket limits rounds of product extension.